Gait Problem Can be Quickly Overcome by The Good Assessment of The Lower Extremity Development in The Children with Hemiplegic Cerebral Palsy - Uygur, Ramazan; Özen, Oğuz Aslan; Baş, Orhan; Toktaş, Muhsin; Songur, Ahmet (Fırat University, 2013)
Objective: In this study, our aim was to investigate the development of the lower extremity by using anthropometric measurements in the children with hemiplegic cerebral palsy (HCP). Material and Method: In our study, lower extremities of 32 children with HCP in the age group 5-12 years and 40 normal children in the same age group were measured anthropometrically. Results: Most of the values for the circumference, length and width of the plegic side of the lower extremity of the children with HCP were significantly lower than those of the unaffected side of the lower extremity of the children with HCP. Nevertheless, all of the values for the circumference, length and width of both the unaffected and the plegic sides of the lower extremity of the children with HCP were significantly lower than those of the lower extremity of the normal children. Conclusion: When compared with normal children, retardation of muscle and bone development due to functional limitation was seen in the lower extremity of children with HCP both on the plegic side and unaffected side. Performing an exercise program of the unaffected side as well as rehabilitation of the plegic side may shorten the process of gaining the ability of walking.

Amaç: Çalışmamızda hemiplejik serebral palsili (HSP) çocuklarda alt ekstremite gelişiminin antropometrik ölçümler kullanılarak incelenmesi amaçlandı. Gereç ve Yöntem: Çalışmamızda 5-12 yaş grubundan 32 HSP'li çocuk ile yine aynı yaş grubundan 40 normal çocuğun alt ekstremitelerinin antro-pometrik ölçümleri yapıldı. Bulgular: HSP'li çocukların plejik taraf alt ekstremite çevre, uzunluk ve çap değerlerinin çoğu HSP'li çocukların sağlam taraf alt ekstremite değerlerine göre önemli derecede düşüktü. Bununla beraber, HSP'li çocukların hem plejik taraf hem de sağlam taraf alt ekstremitelerinin tüm çevre, uzunluk ve çap değerleri normal çocukların alt ekstremite değerlerine göre önemli derecede düşüktü. Sonuç: Fonksiyonel kısıtlılık sonucu HSP'li çocukların hem plejik taraf hem de sağlam taraf alt ekstremite kas ve kemik gelişiminin normal çocuklara göre geri kaldığı görüldü. Yürümenin sağlanması için plejik tarafın rehabilitasyonunun yanında sağlam tarafa da egzersizlerin uygulanması bu süreci kısaltabilir.
Yürüme Sorunu Hemiplejik Serebral Palsili Çocuklarda Alt Ekstremite Gelişiminin İyi Saptanmasıyla Çabuk Aşılabilir